ONLINE STATISTICS SYSTEM FOR PARTICIPANTS IN THE DISCORD MESSENGER USING PYTHON AND POSTGRESQL - Roman R. Krapivin; Linar M. Akhmetov; Marat R. Khamidullin; Gulnara A. Gareeva (International Journal of Advanced Studies, 2022)
The relevance of the topic under consideration is since in one of the Discord channel communities there was a need to collect the activity of channel members for a certain time and duration.